1991
DOI: 10.1210/endo-129-3-1207
|View full text |Cite
|
Sign up to set email alerts
|

Radiotelemetric Monitoring of Hypothalamic Gonadotropin-Releasing Hormone Pulse Generator Activity Throughout the Menstrual Cycle of the Rhesus Monkey*

Abstract: Continuous monitoring of the electrophysiological manifestations of GnRH pulse generator activity was achieved by radiotelemetry throughout the menstrual cycles of unrestrained rhesus monkeys. The characteristic increases in hypothalamic multiunit activity (MUA volleys) associated with each LH pulse measured in the peripheral circulation were of lower frequency during the luteal phase than in the follicular phase of the cycle. Multiunit activity volley frequency increased as functional luteolysis progressed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
70
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 50 publications
2
70
3
Order By: Relevance
“…Previous studies on electrical activity in the hypothalamus during the surge, using radiotelemetric recordings of GnRH pulse generator activity, indicated a decrease in multiple unit activity (MUA) associated with LH surges in monkeys and goats (52,53). This finding contrasts with the present data, which show dramatic increases in GnRH neuron activity associated with the LH surge in mice.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies on electrical activity in the hypothalamus during the surge, using radiotelemetric recordings of GnRH pulse generator activity, indicated a decrease in multiple unit activity (MUA) associated with LH surges in monkeys and goats (52,53). This finding contrasts with the present data, which show dramatic increases in GnRH neuron activity associated with the LH surge in mice.…”
Section: Discussioncontrasting
confidence: 99%
“…Experimental inferences concerning the unique physiological transition that terminates the LF and introduces the luteal phase differ. For example, radiotelemetric monitoring of mediobasal hypothalamic multiunit electrical-bursting activity (a putative physiological correlate of GnRH pulses) suggests that discrete GnRH event frequency decreases or does not change during the preovulatory LH surge in the monkey and rat (22,23). Other analyses based on systemic estimates of LH pulsatility and central monitoring of hypothalamo-pituitary portal-venous and cerebrospinal fluid GnRH pulsatility report amplification of GnRH pulse amplitude and variable acceleration of GnRH secretory-burst frequency during the ascending limb of the LH surge in the rat, monkey, and sheep (8,21,31,36,49).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that electrophysiological manifestations of the GnRH pulse generator are represented as characteristic increases in MUA (MUA volleys) that are exclusively associated with LH pulses in the monkey [8], rat [9] and goat [10,11]. It might be that observed MUA volleys reflect the pulsatile activation of GnRH nerve terminals as they traverse en passant to the ME.…”
mentioning
confidence: 99%